Application of Lean Thinking Development: Case Study over Badan Pendapatan Daerah (BAPENDA), South Tangerang Based on Lean Government - Ketut Sunaryanto; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2019)
Lean thinking is used to analyse manufacturing sector namely lean manufacturing over industrial process. In addition, the development lean thinking over government sector is a right choices to improve quality of government service. Thus, this aimed to test the Lean Government algorithm with Define, Measure, Analysis, Improve, and Control (DMAIC) and Lean Consumption Map (LCM) method over government service. By using comparison completion time over building tax object and registration file document at Badan Pendapatan Daerah (BAPENDA) South Tangerang. The result showed, Lean Government algorithm was successful to assess comparison method with Time Series Plot, Value Added Assessment, and Lean Consumption Map. In this study, we use qualitative research methods and interview with internal and external correspondence, respectively. We found that the DMAIC application and Lean Consumption Map inside the Lean Government algorithm will be improve the time of settlement document and service process over BAPENDA South Tangerang